Materials and Processes for Photocatalytic and (Photo)Electrocatalytic Removal of Bio-Refractory Pollutants and Emerging Contaminants from Waters - Vacca, Annalisa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Water pollution from biorefractory pollutants and emerging contaminants is still a very relevant problem worldwide. Examples of these pollutants include disinfection by-products, pharmaceutical and personal care products, persistent organic chemicals, as well as their degradation products. The occurrence of these contaminants in water has raised increasing concern due to their accumulation and persistence in the environment and the threat they pose to the ecological system and human health. In this Special Issue, papers regarding the advancements in materials and processes for use in the electro- and photoelectrochemical removal of different pollutants from water are collected. The synthesis, characterization and application of materials for use in electrochemical or photoelectrochemical techniques are presented, as well as studies concerning catalytic processes and reaction kinetics.